2020
DOI: 10.1042/bcj20200399
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell polyomavirus small tumour antigen activates the p38 MAPK pathway to enhance cellular motility

Abstract: Merkel cell carcinoma (MCC) is an aggressive skin cancer with high rates of recurrence and metastasis. Merkel cell polyomavirus (MCPyV) is associated with the majority of MCC cases. MCPyV-induced tumourigenesis is largely dependent on the expression of the small tumour antigen (ST). Recent findings implicate MCPyV ST expression in the highly metastatic nature of MCC by promoting cell motility and migration, through differential expression of cellular proteins that lead to microtubule destabilisation, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Furthermore, although not recognized in the KEGG pathway database, the DAGs SULF2, RBFOX3, and COL11A1 have been reported to upregulate the PI3K-Akt signaling pathway and the DAGs ITGA6, SMYD3, and ENC1 have been reported to upregulate the MAPK signaling pathway in other malignancies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. MCPyV small tumor antigen has previously been demonstrated to activate p38 MAPK signaling in MCC, and immunohistochemical findings have demonstrated high degrees of activating AKT phosphorylation in MCC [ 32 , 33 ]. The PI3K-Akt and MAPK signaling pathways both serve oncogenic roles in several malignancies, such as stimulating cellular proliferation, inhibiting apoptosis, promoting tumor invasion and metastasis, and stimulating angiogenesis, which in the case of the MAPK pathway is partially mediated by upregulation of VEGFA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although not recognized in the KEGG pathway database, the DAGs SULF2, RBFOX3, and COL11A1 have been reported to upregulate the PI3K-Akt signaling pathway and the DAGs ITGA6, SMYD3, and ENC1 have been reported to upregulate the MAPK signaling pathway in other malignancies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. MCPyV small tumor antigen has previously been demonstrated to activate p38 MAPK signaling in MCC, and immunohistochemical findings have demonstrated high degrees of activating AKT phosphorylation in MCC [ 32 , 33 ]. The PI3K-Akt and MAPK signaling pathways both serve oncogenic roles in several malignancies, such as stimulating cellular proliferation, inhibiting apoptosis, promoting tumor invasion and metastasis, and stimulating angiogenesis, which in the case of the MAPK pathway is partially mediated by upregulation of VEGFA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vitro virus generation and virus-like particle (VLP) studies, MCV capsids bind to heparin sulfate moieties on host cell surfaces followed by secondary interaction with sialylated glycans [ 25 , 29 ]. MCV utilizes caveolin/lipid raft-mediated endocytosis to transit the host cell plasma membrane but only minor populations of the internalized MCV virions are able to reach the endoplasmic reticulum, which has been suggested to be a bottleneck step during MCV infection [ 30 , 31 ]. It is not clear how MCV traffics from the endoplasmic reticulum to the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PP4c has also been implicated in the regulation of MAPK pathway in Merkel cell polyomavirus (MCPyV) -induced tumorigenesis which is associated with shown that MCPyV ST-mediated p38 MAPK signalling occurs because of its interaction with PP4c. In these cells, PP4c was shown to inhibit MAPK signalling pathway, the interaction between MCPyV ST and PP4c leads to the inhibition of PP4c and the consequent activation of MAPK pathway which in turn promotes cell motility and migration [39]. PP4c has also been shown to act as a negative regulator of NFκB activity in T lymphocytes [40].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%